Pengaruh Pemberian Kapsul Bubuk Daun Kelor Terhadap Sensasi Nyeri DOMS - Samudra, Naufal Allaam; Irawan, Roy Januardi (Jurnal MensSana, 2025)
Delayed Onset Muscle Soreness (DOMS) can lead to muscle stiffness and reduced functionality if not addressed promptly, negatively impacting one's ability to perform daily activities. This research aims to expedite the reduction of muscle pain associated with DOMS through the use of capsules containing Moringa oleifera leaf extract. The study employs a quantitative descriptive approach with a randomized pretest-posttest design. The sample includes students involved in volleyball extracurricular activities, divided into two groups: 10 participants in the treatment group and 10 in the control group. Participants in the treatment group received 1000 mg of Moringa leaf powder capsules daily after engaging in eccentric exercises. Capsules were administered one hour and 24 hours post-exercise. Muscle pain was measured using the Visual Analogue Scale (VAS) one hour before the capsule administration and again 48 hours after the exercise. Results indicated that the treatment group experienced a significant reduction in muscle pain 48 hours post-exercise (mean score: 6 ± 0.816) compared to the control group (mean score: 7.5 ± 0.788), with a p-value of 0.00 (p<0.05).